The book of dust : the secret commonwealth - Pullman, Philip, 1946- (The book of dust, 2019)
Lyra and Malcolm travel beyond the confines of Oxford, across Europe, and into the Levant, searching for a city haunted by daemons and following the trail left by a murdered botanist with information about the nature of Dust.